2020
DOI: 10.1021/acsomega.0c03648
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental Study of the Effect of Different Parameters on the Adsorption and Desorption of Trichloroethylene Vapor on Activated Carbon Particles

Abstract: Trichloroethylene (TCE) is used as a solvent in various industrial processes. During its use, TCE vaporizes and its vapor pollutes the working atmosphere. Its recovery is very important and activated carbon may be used for this purpose. In the present study, experiments were conducted with activated carbon particles for adsorption and desorption of TCE vapor. The adsorption isotherms were measured over a temperature range of 30–100 °C. Also, the effects of particle sizes (d p; 355, 500, and 710 μm), initial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The adsorbent capacity, which is the quantity of adsorbate absorbed by the adsorbent per unit mass or volume of the adsorbent, can be influenced by several factors. pH, dosage, agitation speed, time, temperature, particle size, surface area, and micropore volume of the adsorbent are the parameters that affect the absorbent capacity. In addition, different properties of different metal ions, such as their ionic radius, charge, and electronegativity, change the adsorbent capacity of each metal ion in the same material. , Therefore, the adsorption capacity for each metal ion is different and can be listed as Nd > Fe > Pr > Dy in these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorbent capacity, which is the quantity of adsorbate absorbed by the adsorbent per unit mass or volume of the adsorbent, can be influenced by several factors. pH, dosage, agitation speed, time, temperature, particle size, surface area, and micropore volume of the adsorbent are the parameters that affect the absorbent capacity. In addition, different properties of different metal ions, such as their ionic radius, charge, and electronegativity, change the adsorbent capacity of each metal ion in the same material. , Therefore, the adsorption capacity for each metal ion is different and can be listed as Nd > Fe > Pr > Dy in these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…NMR Analysis. 1 H and 11 B NMR analyses were completed using a Bruker AVANCE III 500 spectrometer equipped with a Prodigy cold probe. The frequency used for 1 H NMR was 500.13 and 160.47 MHz for 11 B NMR.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Remediation of chlorinated aliphatic hydrocarbons (CAHs), such as trichloroethylene (TCE), are primary or co-contaminants in over 50% of superfund sites and brownfields across the United States. , Bioremediation of CAHs by anaerobic reductive dechlorination is one potential remediation technique being researched at the lab scale and in the field. Microbial consortia are key players in bioremediation due to their ability to chemotax toward contaminant sources in the environment, act as self-replicating catalysts, degrade contaminants to low regulatory requirements, and provide low-cost treatment compared to other methods. However, Robinson et al demonstrated that metabolically generated acids in poorly buffered systems could severally inhibit microbial consortia and stop the degradation process before complete dechlorination was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…In adsorption by static batch methods, smaller particle sizes result in higher adsorption capacity and efficiency, since there are more active sites for binding [ 207 ]. Table 4 represents results of studies where the effect of particle size was investigated, and a similar trend was observed.…”
Section: Factors Affecting Adsorption Processmentioning
confidence: 99%